Mexico at the crossroads of natural resource dependence and COP26 pledge: Does technological innovation help?. (August 2022) - Hossain, Md. Emran; Islam, Md. Sayemul; Bandyopadhyay, Arunava; Awan, Ashar; Hossain, Mohammad Razib; Rej, Soumen
Abstract: The nexus between natural resource depletion and environmental quality has been a heated topic of debate among policy experts in recent years. This nexus is crucial to achieve Sustainable Development Goal (SDG) 13 which deals with climate change mitigation. However, the extant literature has not paid due attention to this nexus, particularly in the case of Mexico. Against this backdrop, the present study examines the relationship between ecological footprint and natural resource depletion, economic growth, energy consumption, technological innovation, and foreign direct investment in the Mexican economy. The present research leverages the novel dynamic autoregressive distributed lag (ARDL) simulations approach and uses annual frequency data from 1980 to 2018. Empirical findings from the ARDL bounds test substantiate the presence of long-run association among studied variables. Furthermore, the result of the novel dynamic ARDL simulation does not validate the Environmental Kuznets curve (EKC) hypothesis. Thus, implying that Mexico's economy remains at the scale stage, with a scope of economic expansion relative to environmental quality. However, the Pollution Haven Hypothesis (PHH) is validated. Interestingly, natural resource rent accompanied with energy use and foreign direct investment deteriorate the environmental quality in the short-and long-run. However, technological innovation seems to emanate as a panacea for environmental degradation in the long-run. Result analysis also demonstrates that 10% positive and negative simulation graphs for the studied variables. The Frequency Domain Causality analysis also corroborates the above findings. These findings have far-reaching policy implications for Mexico's sustainable environment amid prudent use of natural resources, which are prescribed in the final section. Highlights: Environmental Kuznets Curve (EKC) hypothesis is not valid for Mexico. Findings support Pollution haven hypothesis (PHH). Natural resources rent instigates the ecological footprint. The intensity of energy use also escalates the ecological footprint. Technological innovation offsets environmental pollution in the long-run.